Documentary repository on the disease COVID-19 (2021)
The Documentary Repository on the COVID-19 disease https://expeditiorepositorio.utadeo.edu.co/handle/20.500.12010/10356 is a bibliographic proposal that seeks to consolidate in an orderly way the scientific, normative and journalistic production on topics related to the SARS-CoV-2 virus to facilitate consultation, usability and use at different academic levels, arrange the contents, differentiating them in access with restrictions and open access in a digital repository.